CAD Electrical process for aerospace harness - Hansson, Anton; Land, Julia (My University, 2022)
This report presents a project done at the start-up company Heart Aerospace. The project is about developing a standardized procedure on how to design cable harness in CATIA V5. Having a faulty cable harness in an aircraft can lead to life threatening danger. Standardized procedures are therefore necessary to minimize the risk of errors. The first step of the project was to learn about the safety and installation requirements for the electrical wire interconnection systems (EWIS). EWIS is the wiring system and the terminations in the aircraft. The second step was to acquire knowledge on cable harness design in CATIA V5. This was gained from Heart Aerospace employees and web-based research. In addition, a pilot project was provided to learn about cable harness design and to find a structure for the standardized procedure. The purpose of the pilot project was to elaborate wiring and documentation between two points, both located in the cockpit avionics bay behind the displays. The third step was to develop the standardized procedure for how to design cable harness. The development resulted in a 110 pages guideline with figure and text format. The guideline was an iterative process based on feedback from Heart Aerospace employees and test results from external students. The guideline was designed to be elemental and can therefore be used by experienced and non-experienced CATIA V5 users. The information about cable harness design are continuously being updated at the company and the guideline will be change with it. The developed guideline is therefore the revision A for Heart Aerospace.
Keywords: Aerospace, cable harness, CAD method, wire installation, EWIS